Developing Question-Based Learning Media by Applying Computational Thinking for Elementary School Students - Muhammad Hazmi Zuhdi; Lala Septem Riza; Erna Piantari (Universitas Pendidikan Indonesia, 2021)
This study aims to introduce question-based computational thinking to elementary school students. The background is the study that education in Indonesia needs to be improved in order to answer the global competition in the 21st century which is full of technological and information developments. In today's era everything is integrated with computers and technology, therefore it is necessary to be equipped with Computational Thinking which is believed to be able to train the brain to get used to thinking logically and structurally so that they are faster. Therefore, the development of Computational Thinking learning media was carried out by teaching using questions consisting of 4 categories and totaling 17 questions which were applied to the media. The media development model used was ADDIE (Analyze, Design, Development, Implementation, Evaluate) with a sample of 6 students from grade 6 SDIT 'Alamy Subang. The results of this study indicate that: The instructional media has been evaluated and rated